Autophagy in renal fibrosis: Protection or promotion? - Dai, Rong; Zhang, Lei; Jin, Hua; Wang, Dong; Cheng, Meng; Sang, Tian; Peng, Chuyi; Li, Yue; Wang, Yiping (Frontiers in Pharmacology, 2022)
Autophagy is a process that degrades endogenous cellular protein aggregates and damaged organelles via the lysosomal pathway to maintain cellular homeostasis and energy production. Baseline autophagy in the kidney serves as a quality control system and is essential for cellular metabolism and organelle homeostasis. Renal fibrosis is the ultimate pathological manifestation of progressive chronic kidney disease. In several experimental models of renal fibrosis, different time points, stimulus intensities, factors, and molecular mechanisms mediating the upregulation or downregulation of autophagy may have different effects on renal fibrosis. Autophagy occurring in a single lesion may also exert several distinct biological effects on renal fibrosis. Thus, whether autophagy prevents or facilitates renal fibrosis remains a complex and challenging question. The review explores the different effects of the dual regulatory role of autophagy on renal fibrosis in different models of renal fibrosis, and provides ideas for future related basic and clinical research.